Pemilihan Kepala Lingkungan Terbaik di Kelurahan Menerapkan Metode Additive Ratio Assessment (ARAS) - Siti Hummairoh; Mesran Mesran; Alwin Fau (STMIK Budi Darma, 2022)
In the Sudirejo-I Subdistrict, an election for the best neighborhood head will be held every year, this is intended as a reward for the neighborhood head for his duties in his area and is expected to be a motivation for each neighborhood head. Generally, the selection of the best kepling is done by selecting several neighborhood heads based on several criteria determined by the kelurahan and the election results are approved by the lurah. So far, the kelurahan selects criteria that have been determined manually and is quite time-consuming, the results obtained are also less than optimal. Based on the problems described above, a Decision Support System (SPK) is needed that can help with the problem of selecting the best neighborhood head in the Sudirejo-I Village because in a decision support system an effective and optimal decision will be produced. Many methods can be used in decision support systems, one of which is the Additive Ratio Assessment (ARAS) method. The ARAS method is a multi-criteria decision-making method based on the concept of ranking using a utility degree by comparing the overall index value of each alternative to the overall optimal alternative index value. In its implementation, the decision support system in selecting the best splitter in the Sudirejo-I Village by implementing the ARAS method is considered very effective because it is able to produce a ranking of the value of each attribute, so that the selection results are more systematic and objective